Determining the Central Cornea Thickness Variations in Glaucoma vs. Non- glaucoma African Population - S. A. Adegbehingbe; B. A. Olusanya; B. G. K. Ajayi; A. O. Ashaye; C. O. Bekibele (Medical Science: Trends and Innovations Vol. 3, 2025)
Background: Central cornea thickness (CCT) is the measurement of the thickness of the central part of the cornea. It has an influence on cornea rigidity and consequently could affect the accuracy of intraocular pressure (IOP) measurement by Goldmann applanation tonometry (GAT). Aim: To determine the pattern of central cornea thickness (CCT) in an indigenous African population attending the glaucoma clinic at University College Hospital (UCH), Ibadan, Nigeria and identify its relationship to specific open angle glaucoma (OAG) entities in order to administer appropriate treatments. Study Design: This is a hospital-based case-control study. Methods: 340 eyes of 170 consecutive glaucoma patients attending the eye clinic and 340 eyes of 170 consecutive non-glaucoma patients attending the general outpatient department (GOPD) clinic of the UCH, Ibadan, Nigeria between August 2009 and June 2010 who met the inclusion criteria were recruited into the study. A detailed ocular examination was performed on all participants. Results: The mean age of the glaucoma group was 55.7 ± 9.9 years compared to 53.3 years ± 8.4 years in the non-glaucoma group. The mean CCT of all eyes was 530µm. The mean CCT was found to decrease with age in both groups. Conclusion: The study confirms there was no significant relationship between central cornea thickness and specific open angle glaucoma. The study also confirms that primary open-angle glaucoma is the most common type of glaucoma in our clinic population and that there was no significant relationship between central cornea thickness and specific open-angle glaucoma. Central cornea thickness was also shown to decrease with age.